196k views
1 vote
3. For g(x) = x - 12 and h(x) = 2x + 9, h(x) – g(x) =​

User Abellina
by
4.9k points

2 Answers

5 votes

Answer:

x+21 that the answer bro

User Chris Trombley
by
4.9k points
6 votes

Answer:

x+21

Explanation:

g(x) = x - 12 and h(x) = 2x + 9,

h(x) – g(x) =​ 2x+9 - (x-12)

Distribute the minus sign

= 2x+9-x+12

Combine like terms

= x +21

User Jim McKeeth
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.